(untitled) - World Trade Organization (New York, 2002)
The Dispute Settlement Reports of the World Trade Organization (WTO) include Panel and Appellate Body reports, as well as arbitration awards, in disputes concerning the rights and obligations of WTO members under the provisions of the Marrakesh Agreement. These are the WTO authorized and paginated reports in English. An essential addition to the library of all practising and academic trade lawyers, and needed by students worldwide taking courses in international economic or trade law.
Keywords: Foreign trade regulation,Nguyên tắc ngoại thương